The Knowledge and Practices of the Absolute and Relative Dental Implant Contraindications of General Dental Practitioners in Riyadh, Saudi Arabia - Ababneh, Khansa Taha; Farook, Fathima Fazrina; Kharashi, Tala Al; Arfaj, Samar Al; Allahim, Renad (European Journal of General Dentistry, 2023)
Objectives General dental practitioners (GDPs) are faced with increasing numbers of patients requesting dental implants (DI) to replace missing teeth. Being the first dental professional consulting with the patient, being knowledgeable about DI contraindications (DIC) would support the development of appropriate treatment plans. This study aimed to investigate the GDPs level of knowledge of a number of DICs. The study was done in Riyadh, KSA.Materials and Methods A structured electronic questionnaire was distributed to GDPs who consented to participate. Participants were asked whether certain systemic and local conditions were considered DIC, and whether such DIC were considered absolute or relative. Descriptive statistics, t-tests, or one-way analysis of variance, and multiple linear regression were used for the statistical analysis (p ≤ 0.05) to assess the association between the sample characteristics and knowledge of DICs.Results Less than half (42%) of the respondents scored 25 to 50%, and only 2% scored 75 to 100%. The highest proportion of correct responses was related to questions regarding old age (74.09%), glycemic categories (68.52%), active chemotherapy (64.07%), and intravenous bisphosphonates (49.86%). The responses were significantly associated with the years of experience, place of graduation, and highest qualification in DI. Based on the linear regression analysis, higher years of practice were associated with less knowledge of DIC (inverse relationship), graduates of Saudi governmental universities scored higher than the other groups of graduates, and holders of a master's degree in DI scored higher compared to holders of other qualifications. In addition, respondents who received lectures and/or laboratory training as part of their undergraduate curriculum had higher scores than the group who did not.Conclusion The level of DIC-related knowledge of the GDPs in Riyadh is generally good but incomplete; it is significantly influenced by the GDPs' years of practice, place of graduation, qualifications, and receiving didactic and laboratory training in the undergraduate programs. More emphasis on DI and DIC is required to improve treatment planning and patient referral.
Keywords: dental implants; contraindications; absolute; relative; general dental practitioners